Biochar improves soil properties and corn productivity under drought conditions in South Korea - Jae-Hyuk Park; Jin-Ju Yun; Seong-Heon Kim; Jong-Hwan Park; Bharat Sharma Acharya; Ju-Sik Cho; Se-Won Kang (Biochar, 2023)
Abstract Biochar has been shown to improve soil properties and plant productivity in soils with inherently low fertility. However, little has been reported for upland corns under dry and wet precipitation regimes. This study investigates the effect of biochar addition on a range of soil physicochemical, biological, and hydrological properties, and corn growth and productivity under agrometeorological drought and wet conditions. Here, experiments were laid out in a randomized complete block design with three replications at two sites during 2017 and 2018 in South Korea. Treatments included (i) CN: control (ii) IF: inorganic fertilizer (N–P–K) at 145–30–60 kg ha−1; (iii) BS: barley straw at 5 t ha−1; (iv) CWBC: corn waste biochar at 5 t ha−1; (v) CWBC + IF: corn waste biochar + inorganic fertilizer; (vi) CWBC + BS: corn waste biochar + barley straw. The year 2017 was relatively dry, whereas the year 2018 was wet. Despite drought conditions in the year 2017, biochar facilitated soil water conservation. However, higher precipitation in 2018 increased  the quantity and distribution of soil water and nutrients in the top 15 cm. Biochar reduced soil bulk density, and increased porosity, cation exchange capacity and total organic carbon in both years but increased total bacterial counts during the dry year only. Bacterial population was generally higher under wet conditions. Similarly, more soil CO2 was emitted in the wet year than in the dry year. Results further indicated that biochar can enhance corn biomass and grain yield regardless of precipitation conditions. The grain index was, however, affected by rainfall and was significantly different across treatments in the year 2018 only. All biomass, grain yield, and grain index were highest in CWBC + IF treatment and lowest under CN treatment. Indeed, biochar addition appeared to improve soil quality and soil conditioning effects in the drought and wet years, ameliorating soil and plant properties. Overall, biochar can improve water and nutrients storage, availability, and uptake, and therefore corn productivity during hydrological extremes. Graphical abstract